The diversity of natural resource governance in the Russian arctic - Ivanova, Aytalina A.; Stammler, Florian M. (Sibirskie istoricheskie issledovaniya, 2017)
Many indigenous peoples in the Arctic have a longer experience of engaging with its resources than Russians or other peoples who have their own states. What are the governance approaches of these people to the natural resources and their territories, and in what ways do these approaches differ from each other? In this article, we analyse the relationship of two Arctic Russian peoples to natural resources governance on their ancestral lands and to regulative practice by the Federal Russian State, which adopted laws based on the idea of extractivism. We demonstrate the value of studying the tradition of leadership and what we call the 'craving for statehood' using two examples, the Sakha and the Nenets people. We explain why the Sakha people try to ensure their participation in the natural resource governance through the adoption of regional laws, while the Nenets concentrate on solving specific problems affecting directly their reindeer herding and fishing lifestyle. This understanding becomes possible by taking into account in detail the history of the culturally specific social structure of a society of a certain people and its own leadership institutions. With this comparison in the article, we demonstrate an unexpectedly rich diversity of natural resource governance and non-Russian legal traditions in the 'ethnic' Russian Arctic. It is worth nothing that all this diversity unfolds within the general framework of a single legal space under the umbrella of the constitution of the Russian Federation as a post-Westphalian nation state.